2015
DOI: 10.1155/2015/580718
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Determinants of Forest to the Abundance ofLutzomyia longiflocosain Tello, Colombia

Abstract: Lutzomyia longiflocosa is considered the most likely vector of cutaneous leishmaniasis in the sub-Andean region of the upper valley of the Magdalena River between 1,000 and 2,000 meters in the Department of Huila, Colombia. L. longiflocosa is anthropophilic, has endophagic behavior, and is especially important since its dominance in epidemics recorded in the last decade in the departments of Huila, Tolima, and the outbreak in Norte de Santander. The aim of our work is to identify ecological determinants in for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…longiflocosa. This negative association was reported in another study where ecological variables linked to forest microhabitats ("outdoors")were described and confirmed that regional levels of temperature and precipitation are determinants in the abundance of this species [23,24]. In this study, although the values of temperature were in the rank proposed for the same study (18˚C-19.9˚C), the association was not obvious.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
“…longiflocosa. This negative association was reported in another study where ecological variables linked to forest microhabitats ("outdoors")were described and confirmed that regional levels of temperature and precipitation are determinants in the abundance of this species [23,24]. In this study, although the values of temperature were in the rank proposed for the same study (18˚C-19.9˚C), the association was not obvious.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 86%
“…Staurastrum is usually from oligotrophic environments with low pH, however, it can be registered in eutrophic systems; no nutrient influenced the dynamics of the temporal densities of Staurastrum, on the contrary, it is believed that they generate ecological strategies with other species of the same genus for the dynamics of population growth [33], and other taxonomic species such as an insects [34]. As for the other genera that have peaks of abundance, it could only be observed that Melosira and Fragilaria decrease their abundance when the water temperature increases [35].…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the research is to determine the degree of adoption of outsourcing of logistics operations within the city of Neiva. A sample of 100 companies from different economic sectors is contemplated according to Table 2; to these companies an instrument is applied with the same objective of measuring the degree of outsourcing of the logistics processes, which is given an internal validation supported in a reliability analysis of cronbach coefficient [18], [19]. The 100 companies identified for the analysis, domiciled in the city of Neiva are part of the following productive sectors: transport, services, and industrial production, fish farming, oil & gas, financial, public sector, construction, trade, automotive and agroindustrial [20].…”
Section: Methodsmentioning
confidence: 99%